Can anthropometric and physiological performance measures differentiate between olympic selected and non-selected Taekwondo athletes? - Wheeler, K.; Nolan, E.; Ball, N. (International Journal of Sports Science and Engineering, 2012)
This study examined whether anthropometric and physiological performance measures differentiate between Olympic selected and non-selected athletes. Height, body mass, skinfold thickness, strength (squat, bench press and bench pull), power (counter-movement jump, single leg counter-movement jump and 20 m sprint) and aerobic performance (shuttle test) from 10 national squad athletes was collected at the selection camp prior to the Olympic Games. Power, velocity and acceleration profiles during bench throw, bench pull and squat jump were also collected using a linear encoder. Results demonstrated that anthropometric, strength, power and aerobic performance measures could not differentiate between Olympic selected and non-selected athletes. Male Olympic selected athletes displayed a decreased power profile for bench pull and squat jump and only limited improvements in the bench throw compared to non-selected athletes. Power profiles for the bench pull and squat jump but not the bench throw could differentiate between female Olympic selected and non-selected athletes. It was concluded that anthropometric and physiological performance measures cannot consistently differentiate between Olympic selected and non-selected athletes.